Active disturbance rejection control for optoelectronic stabilized platform based on adaptive fuzzy sliding mode control. (June 2022) - Sui, Shuaishuai; Zhao, Tong
Abstract: This paper proposes a method that combines active disturbance rejection control (ADRC) and adaptive fuzzy sliding mode control (AFSMC), which is beneficial for the optoelectronic platform to enhance the target tracking capability. A servo system model based on the LuGre friction is first established. The AFSMC controller estimates the unknown part of the platform, and the fuzzy approximator can reduce chattering. Then, an ADRC controller based on Back-Propagation neural network tuning is designed and compared with the empirical method, which makes the system's tracking accuracy higher. Lyapunov's theorem and Barbara's lemma are forceful methods to prove engineering stability. Simulations illustrate that the influence of external disturbances on the optoelectronic platform can be suppressed, thereby enhancing the disturbance isolation of the controller. Highlights: The control scheme with double speed loop can improve tracking performance. The adaptive fuzzy sliding mode controller can estimate model nonlinearities and torque disturbances. The ADRC controller using neural network tuning can suppress external disturbances faster than traditional tuning. The simulations show that the control method is effective.